Enhancing electrical conductivity of RuO2 nanosheet-coated films by enlarging the nanosheet area - Doh Won Jung; Chan Kwak; Hee Jung Park; Weon Ho Shin; Hyun Sik Kim; Jong Wook Roh; Sungwoo Hwang; Jongmin Lee; Kimoon Lee; Changhoon Jung; Dong-Su Ko; Se Yun Kim (Alexandria Engineering Journal)
This study focused on enhancing the electrical conductivity of metal oxide nanosheet films by increasing the size of the nanosheets to promote the electron flow in the desired in-plane direction. We developed a method for increasing the size of RuO2 metal oxide nanosheets, a 2D material, by controlling the heat-treatment process. The size of the RuO2 nanosheets increased from 0.7 to 3.5 μm by modifying the heat-treatment conditions of KxRuO2, which was used as the precursor material. As a consequence, the electrical conductivity of the large-sized-RuO2 nanosheet-coated films was eight times higher than that of their small-sized counterparts. This lower resistance was attributed to the minimal number of contacts required for electron flow; the contact resistance between the nanosheets being higher than the intrinsic resistance. The proposed approach for enhancing the conductivity of metal oxide 2D materials is very promising and is expected to significantly contribute to the development of advanced flexible electronic devices.